Prehospital Recognition and Management of Pneumothorax: Advancing Emergency Medical Services Practice Through Clinical Assessment, Rapid Intervention, and Evidence-Based Guidelines - Geesi, Ali Mohd Taher; Nada Fahad Mutlaq Almutlaq,; Ahmed Suliman Alfaifi,; Mansour Mayudh S. Alharthi,; Fahad Obed Alharbi,; Atallah Zafran Altarfawi,; Amjad Mudhayyif Alsufyani,; Seham Abdullah Alsunbul,; Naif Madallah Alanazi,; Aisha Hamad Mahmoodi, (Saudi Journal of Medicine and Public Health, 2025)
<span style="font-size: 11pt; font-family: Aptos; background-color: transparent; font-weight: bold; font-variant-numeric: normal; font-variant-east-asian: normal; font-variant-alternates: normal; font-variant-position: normal; font-variant-emoji: normal; vertical-align: baseline; white-space-collapse: preserve;">Background:<span style="font-size: 11pt; font-family: Aptos; background-color: transparent; font-variant-numeric: normal; font-variant-east-asian: normal; font-variant-alternates: normal; font-variant-position: normal; font-variant-emoji: normal; vertical-align: baseline; white-space-collapse: preserve;"> Traumatic pneumothorax is the second most common chest injury, with approximately 50,000 cases annually in the US. It is a life-threatening condition that can rapidly progress to tension physiology, leading to obstructive shock and cardiac arrest. Effective prehospital management by Emergency Medical Services (EMS) is critical for patient survival, as timely intervention can prevent respiratory and hemodynamic collapse. <span style="font-size: 11pt; font-family: Aptos; background-color: transparent; font-weight: bold; font-variant-numeric: normal; font-variant-east-asian: normal; font-variant-alternates: normal; font-variant-position: normal; font-variant-emoji: normal; vertical-align: baseline; white-space-collapse: preserve;">Aim:<span style="font-size: 11pt; font-family: Aptos; background-color: transparent; font-variant-numeric: normal; font-variant-east-asian: normal; font-variant-alternates: normal; font-variant-position: normal; font-variant-emoji: normal; vertical-align: baseline; white-space-collapse: preserve;"> This review aims to synthesize current evidence and guidelines for the prehospital recognition and management of traumatic pneumothorax, focusing on clinical assessment, rapid intervention strategies, and the advancement of EMS practice through technology and protocol optimization. <span style="font-size: 11pt; font-family: Aptos; background-color: transparent; font-weight: bold; font-variant-numeric: normal; font-variant-east-asian: normal; font-variant-alternates: normal; font-variant-position: normal; font-variant-emoji: normal; vertical-align: baseline; white-space-collapse: preserve;">Methods:<span style="font-size: 11pt; font-family: Aptos; background-color: transparent; font-variant-numeric: normal; font-variant-east-asian: normal; font-variant-alternates: normal; font-variant-position: normal; font-variant-emoji: normal; vertical-align: baseline; white-space-collapse: preserve;"> A comprehensive literature review was conducted, analyzing established trauma protocols, clinical studies on intervention efficacy, and data on evolving prehospital technologies such as point-of-care ultrasound (POCUS). The pathophysiological basis for different pneumothorax types (simple, tension, open) and corresponding management techniques were evaluated. <span style="font-size: 11pt; font-family: Aptos; background-color: transparent; font-weight: bold; font-variant-numeric: normal; font-variant-east-asian: normal; font-variant-alternates: normal; font-variant-position: normal; font-variant-emoji: normal; vertical-align: baseline; white-space-collapse: preserve;">Results:<span style="font-size: 11pt; font-family: Aptos; background-color: transparent; font-variant-numeric: normal; font-variant-east-asian: normal; font-variant-alternates: normal; font-variant-position: normal; font-variant-emoji: normal; vertical-align: baseline; white-space-collapse: preserve;"> Prehospital recognition relies on a high index of suspicion based on mechanism of injury and signs like hypoxia, unilateral absent breath sounds, and hypotension. Needle thoracostomy remains the lifesaving intervention for suspected tension pneumothorax, with a growing preference for the 4th/5th intercostal space mid-axillary approach over the traditional 2nd intercostal mid-clavicular site due to higher success rates. For open ("sucking") chest wounds, application of an occlusive dressing—now often a commercially available, fully sealed device—is standard. The integration of portable POCUS shows promise for earlier field diagnosis but requires further outcome validation. <span style="font-size: 11pt; font-family: Aptos; background-color: transparent; font-weight: bold; font-variant-numeric: normal; font-variant-east-asian: normal; font-variant-alternates: normal; font-variant-position: normal; font-variant-emoji: normal; vertical-align: baseline; white-space-collapse: preserve;">Conclusion:<span style="font-size: 11pt; font-family: Aptos; background-color: transparent; font-variant-numeric: normal; font-variant-east-asian: normal; font-variant-alternates: normal; font-variant-position: normal; font-variant-emoji: normal; vertical-align: baseline; white-space-collapse: preserve;"> Optimal prehospital outcomes depend on systematic assessment, protocol-driven decision-making, and proficiency in critical interventions. While techniques and equipment evolve, the cornerstone of care is the EMS provider's ability to recognize life-threatening physiology and act decisively. Ongoing training, research, and interdisciplinary collaboration are essential to standardize and advance prehospital trauma care.